REPRESENTATION OF CONSUMERISM IN GRABFOOD ADVERTISEMENT: A CRITICAL DISCOURSE ANALYSIS - Bontisesari Wahyoedi (Journal of English Language and Culture, 2022)
The trend of digital advertising has risen significantly as the use of internet is increasing. It contributes to the way people shape their lifestyle and perceive themselves as a part of the society. Due to its significant role in influencing the audience, this article aimed to reveal an ideological representation in a digital advertisement. The object of this article was Grabfood advertisement published in YouTube which contained both linguistics and visual aspects. Hence, this descriptive qualitative study adopted Fairclough’s Critical Discourse Analysis as the theoretical framework to analyze the data. The results showed that there is a representation of consumerism identified in Grabfood advertisement. This ideological representation encourages the audience to consume more by glorifying the consumptive behavior. The advertisement intended to influence the audience subconsciously that by purchasing goods through its product service would be rewarding and would save them more money. Subsequently, through the number of selling points shown in the advertisement, both linguistically and visually, it manages to deliver its purpose in persuading and leading the audience to more consumption. By analyzing the advertisement critically, we can equip ourselves with more understanding on the process of product advertisement, so that the meanings behind the surface of the advertisement can be identified and responded wisely.